DAMPAK PEMBERIAN TUNJANGAN KINERJA DAERAH DALAM MENINGKATKAN KINERJA PNS DI KABUPATEN LAMANDAU (Journal Ilmu Sosial, Politik dan Pemerintahan, 2015)
The research aims to determine the impact of local performance allowance to improve the performance of employees in the district secretariat office lamandau section Administration of the economy and SDA. The research types were descriptive with qualitative approach. With data collecting techniques are observation, interview, and study of documentation. The validity test of the data used source triangulation technique. The data analysis technique was interactive; they are data collection, data reduction, data presentation, and conclusion. The research results showed that The impact of providing local performance allowances to improve performance for employees in the district secretariat office lamandau in the administration of the economy and SDA, that can be seen from indicators, namely (1) Quantity, the employees work based on employee’s performance target (SKP) and the daily performance report (LKH) (2) Quality, the result of their work can be categorized by their performance (3)thepresenceandactivities areincreasing,theemployeescomeandbacktohomebasedontheofficerule,(4)the cooperation, the employees can do the good cooperation with the senior or workmate, (5) Employee economy, Employees feel satisfied and can improve employee performance.